The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/lary.23653
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of airflow patterns in nose models with differently localized septal perforations

Abstract: The numerical simulations demonstrate significantly disturbed intranasal airflow patterns due to SPs. This fact may contribute to crusting and nosebleed due to dehydration of the nasal mucosa. The location and size of the SP are crucial for the impact on disturbed airflow pattern and therefore the patients' complaints. Anterior caudal SPs seem to be the worst. Surgical closure of SPs or simply changes in the site and size of the SP if a complete closure is surgically impossible makes sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
1
26
0
4
Order By: Relevance
“…Velocity contours and streamline patterns within the NSPs (Fig. ) revealed that the velocity peak did not always appear in the center‐to‐posterior regions as suggested by previous studies . For instance, the overall velocity magnitude was highest in the dorsal region for patient 5.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Velocity contours and streamline patterns within the NSPs (Fig. ) revealed that the velocity peak did not always appear in the center‐to‐posterior regions as suggested by previous studies . For instance, the overall velocity magnitude was highest in the dorsal region for patient 5.…”
Section: Resultssupporting
confidence: 56%
“…The maximum WSSs were consistently located at the posterior margin of the perforation. Lindemann et al . also evaluated the characteristics of 3 simulated septal perforations (anterior caudal, anterior cranial, posterior caudal) virtual created on a healthy 50‐year‐old male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most earlier CFD studies were limited in clinical value as they were all based on virtual perforations of healthy controls or non‐NSP patients. For example, Lindemann et al evaluated the airflow characteristics by virtually creating NSPs at 3 different locations (anterior caudal, anterior cranial, and posterior caudal) on a healthy nasal model. Their CFD results show that the anterior caudal NSP led to severe flow changes with high flow velocities, and seemed to be the worst location among all other tested cases.…”
Section: Discussionmentioning
confidence: 99%
“…Using fluid flow properties such as airflow velocity, wall shear stress, and heat flux, CFD has demonstrated utility in assessment of upper respiratory tract and airway reconstructive procedures . However, most previous CFD studies on NSPs addressed virtual perforations of non‐NSP subjects or involved a single NSP patient model . In our previous CFD analysis of nasal airflow in 10 NSP patients we found that the high wall shear stress along the posterior margin of the NSP may lead to symptomatology.…”
mentioning
confidence: 95%